EFFECT OF TEACHING AIDS ON STUDENTS’ ACADEMIC PERFORMANCE IN ENGLISH LANGUAGE IN SELECTED PUBLIC SENIOR SECONDARY SCHOOLS IN KANO METROPOLIS: IMPLICATION FOR POLICY MAKING - Mera, Muhammad Satatu (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
The paper examined the effect of teaching aids on students’ academic performance in English language in selected public senior secondary schools in Kano metropolis, Nigeria. Three research Questions, three objectives and three research hypotheses guided the study. Experimental research design was adopted for the study. Population of the study consisted of five public senior secondary schools in Kano metropolis with a total of 1390 SS 2 students. Research advisor (2006) was used to determine the required sample size for the study and it recommended a sample size of 306. A simple random sampling technique was used to select the sample size required by the study Data was collected using an instrument titled “Utilization of Teaching Materials and Academic Performance Questionnaire (UTMAPQ)”. Reliability of the instrument was obtained using a test-retest method within an interval of 6 weeks. A reliability index of 0.74 was obtained through the Cronbach Alpha Co-efficient. The instrument has 20 items which are open ended questions. Hypotheses generated were tested using independent T-test at 0.05 level of significance. Findings from the study indicated among others that: Audio-visual teaching aids have statistically significant positive effect on public secondary school students’ academic performance in Kano metropolis. The study recommended among others that: Instructional materials such as print media and audio-visuals should be made available to teachers for effective teaching and learning.